К вопросу об источниках развития скелетных мышц рыб - Борисов, И.Н. (Вестник зоологии, 1968)
An investigation of the sources of development of skeleton muscles of Acipense-riformes, Selachii and Teleostei showed that in Teleostei the dermatome takes part in the formation of muscle fibres of the myotome and a body wall. The prospective value of the dermatome material in Teleostei is wider than in Acipenseriformes and Selachii in which the dermatome cells give only the basic tissues. It is also established that the ventral processes of the somites of Teleostei are formed of the dermatome material, and those of Acipenseriformes and Selachii — of the special parts of somites, of the ventral growing points. The ventral processes of the somites are not equivalent in various vertebrates.